(untitled) (TAJ: Journal of Teachers Association, 2010)
3 cases of chiari malformation type-I were presented with classical picture of spasticity, quadriparesis and dissociated sensory loss and were operated ( Craniovertebral junction decompression by midline suboccipital craniectomy with removal of C1 arch and duroplasty). All the 3 patients were improved. Among them one patient recovered with some morbidity for postoperative other diseases. TAJ 2010; 23(1): 84-86